2019
DOI: 10.26599/jnr.2019.9040009
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory ensheathing cell transplantation improving cerebral infarction sequela: a case report and literature review

Abstract: Stroke is the second leading cause of death and the main cause of long-term disability in the world. Therefore, treatment of the sequelae of stroke is one of the most important challenges in clinical neurotherapy. A 63-year-old Chinese woman with inarticulateness and right limb physical activity disorder for more than 4 months received olfactory ensheathing cells (OECs)-based neurorestorative therapy during the stay in hospital. Her neurological functions improved during 1-year follow-up. This case report show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…(2) Cell therapy, such as intravenous or arterial injection of monocytes cells and mesenchymal stromal cells [38][39][40][41][42][43][44][45][46][47], injection of olfactory ensheathing cells (OECs) into olfactory sub-mucosa [48], and neural stem cells injection around the diseased region [49][50][51], is suitable for patients with stroke with mild, moderate, and severe neurological damage. Recent studies on high-level evidence-based medicine did not show the neurorestorative capability of mesenchymal stem cells for stroke during the recovering phase.…”
Section: Recovery Phasementioning
confidence: 99%
“…(2) Cell therapy, such as intravenous or arterial injection of monocytes cells and mesenchymal stromal cells [38][39][40][41][42][43][44][45][46][47], injection of olfactory ensheathing cells (OECs) into olfactory sub-mucosa [48], and neural stem cells injection around the diseased region [49][50][51], is suitable for patients with stroke with mild, moderate, and severe neurological damage. Recent studies on high-level evidence-based medicine did not show the neurorestorative capability of mesenchymal stem cells for stroke during the recovering phase.…”
Section: Recovery Phasementioning
confidence: 99%
“…Zhang et al [15] showed that the intracerebral injection of neural stem cells improved the neurological functions of patients with paralysis after an ischemic stroke. Guo et al [16] reported that transplanting olfactory ensheathing cells in a patient with cerebral infarction sequela could improve his quality of life. Savitz et al [17] conducted a randomized, sham-controlled, parallelgroup, multicenter clinical trial for patients with subacute ischemic strokes by intra-arterially delivering autologous bone marrow-derived ALD-401; but reported no differences between cell therapy and the control.…”
Section: Achievements and Progress In Clinical Neurorestorative Therapies 41 Cell Therapymentioning
confidence: 99%
“…Similar to astrocytes and oligodendrocytes in the central nervous system and Schwann cells in the peripheral nervous system, OECs induce olfactory axonal growth and guide the elongation of axons through the barrier between the peripheral and central nervous systems. OECs are involved in the remyelinating process, facilitate the passage of regenerating axons of nerve fibers through glial scar tissue, exhibit unique neurorestorative effects in basic, preclinical treatment of the central nervous system , and improve the quality of life for patients with neurological damage or diseases [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Olfactory Ensheathing Cellmentioning
confidence: 99%